INVENTARISASI HAMA PADA PERLAKUAN DOSIS PUPUK KANDANG TERHADAP TANAMAN PADI KETAN PUTIH (Oryza sativa L glutinosa) - Setiyawan, Arif; Santosa, Sartono Joko; Triyono, Kharis (Innofarm:Jurnal Inovasi Pertanian, 2020)
The research on "The inventory of pests in the treatment of dosage manure for white glutinous rice crops (Oryza sativa L glutinosa)" was carried out from November 10th, 2019 until February 27th, 2020 in Donohudan village, Ngemplak District, Boyolali. This research aims to known the kinds of pests that attack white glutinous rice crops (Orzya sativa L glutinosa) as well as the degree of damage to the treatment of dosage manure. The research used a Random Complete Blok Design (RCBD) single factor consisting of 10 kinds treatments and repeated 3 times. The parameters observed are : kind of pests that attacked, the intensity of pest damage, the number of tillers per clump, weight of the dried grain harvest per plot, weight of 1000 grains. The results showed that (1) The types of pests that attack the treatment of manure doses of white glutinous rice plants (Oryza sativa L glutinosa), namely locust pest, stem borer pests, and stinky bugs pest. (2) Treatment of manure goat dose 1.35 kg / plot (K3) is a dose of manure with the lowest level of pest attack on parameters the intensity of locust pest damage, stem borer pests, and stinky bugs pest. (3) The treatment of manure chicken has a significant effect on yields is the number of tillers per clump, the weight of the dried grain harvest per plot, and the weight of 1000 grains.